PELATIHAN MENULIS KREATIF, INSPIRATIF, DAN INOVATIF 4.0 MELALUI W-MODEL CREATIVE, INSPIRING, INNOVATIVE WRITING TRAINING 4.0 THROUGH W-MODELS - Wido Hartanto (JURNAL MASYARAKAT NEGERI ROKANIA, 2020)
So far, writing skills are mandatory abilities that must be mastered by teachers, both scientific and non scientific writing. The importance of teachers having the ability to write later will be their own stories for students being taught. Students will certainly be more motivated if a teacher is able to produce their own work as teaching material. However, during writing sometimes the teacher encounters obstacles. One of the schools that continues to grow, but has limited resources is the Ghilmani Integrated Islamic Elementary School Surabaya. SDIT Ghilmani is an elementary school that continues to grow. As the development of this school continues to require teachers who are creative and can provide interesting lessons. The goal is of course to make students enthusiastic about learning. The implementation method uses a coaching clinic, so participants can practice directly. Broadly speaking activities refer to the 3C concept, namely Creativity, Communication, and Create. The trainees also presented the concept of W-Model in writing. SDIT Ghilmani teacher was able to produce unique and crisp works